PENGARUH PELATIHAN DAN SIKAP KEWIRAUSAHAAN TERHADAP PENDAPATAN PELAKU UMKM DI KOTA PONTIANAK - Elisa Br Siringo-ringo; Herkulana Herkulana; M. Basri (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2022)
MSME actors need to make several efforts to strengthen and face the global market, such as improving the quality of human resources, and the entrepreneurial attitude of MSMEs. Pontianak City has a number of MSMEs that have risen to improve their lives through business development. This is supported by various Pontianak City training centers to improve the quality and human resources to run MSMEs. One of them is carried out by the Office of Investment, Manpower and PTSP of Pontianak City. The approach in this study is a quantitative approach with survey methods and path analysis techniques. The results showed that training (X1) had a direct effect on income (Y). The correlation value of 0.486 category is quite strong. The sig value is 0.046 < 0.05 with a large direct effect of 5.4289%. Training (X1) has a direct effect on Entrepreneurial Attitudes (X2). The correlation value is 0.424, the category is quite strong, the sig value is 0.000 <0.05, and the direct effect is 17.9776%. Entrepreneurial Attitude (X2) has a direct effect on Income (Y). The correlation value is 0.486, the category is quite strong, the sig value is 0.004 <0.05 with a large direct effect of 11.4921%. The equation for path analysis of the training variable on entrepreneurial attitudes is X2 = 0.424X1 + 0.821. The path analysis equation for the variable of Entrepreneurship Training and Attitude towards Income is Y = 0.233X1 + 0.339X2 + 0.764.